Cryostimulation for Post-exercise Recovery in Athletes: A Consensus and Position Paper - Bouzigon, Romain; Dupuy, Olivier; Tiemessen, Ivo; De Nardi, Massimo; Bernard, Jean-Pierre; Mihailovic, Thibaud; Theurot, Dimitri; Miller, Elzbieta Dorota; Lombardi, Giovanni; Dugué, Benoit Michel (Frontiers in Sports and Active Living, 2021)
Recovery after exercise is a crucial key in preventing muscle injures and in speeding up processes to return at the homeostasis level. There are several ways of developing a recovery strategy with the use of different kinds of traditional and up-to date techniques. The use of cold has traditionally been used after physical exercise for recovery purposes. In the recent years, the use of whole-body cryotherapy/cryostimulation (an extreme cold stimulation lasting 1-4 min and given in a cold room at a temperature comprised from -60 to -195°C) has tremendously increased for such purposes. However, there are controversies about the benefits that the use of this technique may provide. Therefore, this paper describes what is whole body cryotherapy/cryostimulation, reviews and debates the benefits that its use may provide, presents practical considerations and applications, and emphasizes the need of customization depending on the context, the purpose, and the subject characteristics. This review is written by international experts from the working group on whole body cryotherapy/cryostimulation from the International Institute of Refrigeration.